2005
DOI: 10.1002/jmv.20342
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting patterns of hepatitis C virus infection in two regions from Tunisia

Abstract: This report is a population-based study describing the pattern of hepatitis C virus (HCV) infection in two distinct regions in Tunisia. The study included a total of 11,507 individuals sampled in 1996 from both genders, all age groups, urban and rural settings belonging to 2,973 families. HCV infection was assessed by commercial enzyme immunoassay (EIA) and immunoblot assays and detection of HCV RNA by PCR. HCV genotypes and subtypes were determined by sequencing in the 5'-untranslated region (UTR) viral genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
21
3
6

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 50 publications
6
21
3
6
Order By: Relevance
“…In the present study, 90.4% of the anti-HCV positive patients were viremic and this figure was higher than estimated for the general European and Tunisian HCV population, where 80% is suggested [Hinrichsen et al, 2002;Mejri et al, 2005]; it was even higher than in Tunisian dialysis patients in whom viremia was found in 78.9% [Ben Othman et al, 2004]. Nevertheless, a Spanish study reported that 3 years after acute hepatitis C infection, 87.5% of hemodialysis patients remained HCV-RNA positive [Espinosa et al, 2002].…”
Section: Discussioncontrasting
confidence: 81%
“…In the present study, 90.4% of the anti-HCV positive patients were viremic and this figure was higher than estimated for the general European and Tunisian HCV population, where 80% is suggested [Hinrichsen et al, 2002;Mejri et al, 2005]; it was even higher than in Tunisian dialysis patients in whom viremia was found in 78.9% [Ben Othman et al, 2004]. Nevertheless, a Spanish study reported that 3 years after acute hepatitis C infection, 87.5% of hemodialysis patients remained HCV-RNA positive [Espinosa et al, 2002].…”
Section: Discussioncontrasting
confidence: 81%
“…Age was found out to increase the risk of carrying anti-HCV in the general population of Tunisia [9]. Male sex was not a risk factor and this is consistent with the results of a study [31] that found no difference in the prevalence of HCV in the general population according to sex.…”
Section: Seroprevalency Of Transfusion-transmissible Infections In Rdsupporting
confidence: 89%
“…The same study [31] found no significant difference between the prevalency of HCV patients in family contact with the virus seropositive members, and that in the entire study population.…”
Section: Seroprevalency Of Transfusion-transmissible Infections In Rdmentioning
confidence: 78%
See 1 more Smart Citation
“…This variation is due to several factors such as blood transfusion, intravenous drug users (IVDU), and lapses of universal precautionary measures. In Tunisia, epidemiological and previous phylogenetic studies conducted on both healthy and HCV infected subjects, reported a large predominance of genotype 1b (4,10,12,26). Few epidemiological studies have focused on HCV-4 infection in Tunisia.…”
Section: Discussionmentioning
confidence: 99%